Design of Automatic Transfer Switch System Solar Power Plant – PLN (Universitas Muhammadiyah Yogyakarta, 2023)
The utilization of solar power for generating energy is increasing in scale. The Solar Power Plant (SPP) operating system comprises On Grid, Off Grid, and Hybrid systems. To successfully execute a power supply transfer operation, it is important to do thorough study. The transfer process is automated by the utilization of voltage sensors. The voltage sensing is derived from the output of both the SPP system and the PLN (Indonesian State Electricity Company) system. This study involved conducting prime SPP (Self-Paced Reading) and prime PLN (Picture Naming) tasks. The stress analysis technique is conducted during transfer in both primes. When converting SPP to PLN and transferring from PLN to SPP, voltage measurements are conducted if the SPP is in its prime state. When the power line network (PLN) is in its optimal state, voltage measurements are conducted during the transition from PLN to the solar power plant (SPP) and vice versa. When the SPP is in its prime state, the average voltage during the transfer from SPP to PLN is at 217.8 V, as indicated by the measurement findings. The average voltage for transferring power from the power grid (PLN) to the power plant (SPP) is at 225.4 V. During the peak power load period, the average voltage transferred from the power grid (PLN) to the power plant (SPP) is at 220.18 V, whereas the average value when moving from SPP to PLN is at 220.12 V. At the prime PLN, there is a minor voltage variance due to the higher stability of the PLN voltage.